ACCOUNTING FOR CLIMATE CHANGE AND OPERATIONAL PERFORMANCE OF QUOTED OIL AND GAS FIRMS IN NIGERIA AND SOUTH AFRICA (Journal of Global Accounting, 2023)
This research work examined the topic: Accounting for climate change and operational performance of quoted oil and gas firms in Nigeria and South Africa. Specifically, this study assessed the relationship between greenhouse gas, carbon emissions, environmental issues, revenue growth, return on investment, profit margin, respectively for the period 2013 – 2022. The reason for this study is to establish new empirical findings to bridge the identified gaps observed in the literature review. This study is anchored on the contingency theory. Few empirical works were reviewed for this study. Ex – post facto research design was employed. The population of this study is twenty-seven (27) quoted oil and gas firms in Nigeria and South Africa as at 31st December, 2022. Inferential statistics of the stated hypotheses were analyzed with the aid of E-View 9.0 statistical software, using: co-efficient of correlation and regression analysis. Three null hypotheses were formulated. Results revealed that accounting for climate change does not have significant effect on revenue while positive significant was observed on return on investment. Net profit margin shows negative at 5% level of significance. Climate change based accounting mostly falls under non-financial reporting, which means it focuses on disclosing environmental, social, and governance (ESG) performance. The study recommended amongst others that Oil and Gas firms could conduct regular risk assessments to identify climate-related risks and their potential impacts on the company's operations and profitability to ensure that risk-mitigating strategies would not only manage risks, but also ensure business continuity and profitability that would benefit the stakeholders.
Keywords: Climate change; Revenue growth; Carbon accounting; Environmental problems; Return on investment; profit margin